A new hybrid method for time series forecasting: AR-ANFIS - KIZILASLAN, BUSENUR (SPRINGER LONDON LTD, 2018)
In this study, a new hybrid forecasting method is proposed. The proposed method is called autoregressive adaptive network fuzzy inference system (AR-ANFIS). AR-ANFIS can be shown in a network structure. The architecture of the network has two parts. The first part is an ANFIS structure and the second part is a linear AR model structure. In the literature, AR models and ANFIS are widely used in time series forecasting. Linear AR models are used according to model-based strategy. A nonlinear model is employed by using ANFIS. Moreover, ANFIS is a kind of data-based modeling system like artificial neural network. In this study, a linear and nonlinear forecasting model is proposed by creating a hybrid method of AR and ANFIS. The new method has advantages of data-based and model-based approaches. AR-ANFIS is trained by using particle swarm optimization, and fuzzification is done by using fuzzy C-Means method. AR-ANFIS method is examined on some real-life time series data, and it is compared with the other time series forecasting methods. As a consequence of applications, it is shown that the proposed method can produce accurate forecasts.
Keywords: Adaptive network fuzzy inference system; Autoregressive model; Fuzzy inference system; Time series; Particle swarm optimization; Fuzzy C-Means; NEURAL-NETWORK; FUZZY; SUPPORT; SYSTEMS; MODEL; LOAD